It’s All Critical: Acting Teachers’ Beliefs About Theater Classes - Goldstein, Thalia R.; Young, DaSean L.; Thompson, Brittany N. (Frontiers in Psychology, 2020)
Acting classes and theatre education have long been framed as activities during which children can learn skills that transfer outside the acting classroom. A growing empirical literature provides evidence for acting classes’ efficacy in teaching vocabulary, narrative, empathy, theory of mind, and emotional control. Yet these studies have not been based in what is actually happening in the acting classroom, nor on what acting teachers report as their pedagogical strategies. Instead, previous work has been unsystematic and fragmented in its measured transfer outcomes, and absent mechanistic explanation. Expanding research on this topic requires more grounding in teachers’ beliefs about the acting classes they teach, as well as observation of the classes themselves. As a first step, we surveyed 173 acting teachers online, asking them about the activities within acting classes they believed caused change in their students, as well as which outcomes they believed were changed as a result of acting classes. Teachers taught across educational levels (elementary to professional) and had a variety of training in teaching acting. Overall, teachers rated almost every activity within classes as important for and causing impact on students, and almost every outcome as being positively influenced as a result of acting class. When forced to rank order outcomes, teachers focused on collaboration, communication, creativity, confidence, and empathy as most likely to change. Teachers rated importance of class activities and outcomes differently depending on what level they taught. This study shows the difficulty of surveying highly motivated teachers, given the globally high rankings, but also proposes candidate psychological skills likely to change as a result of acting classes, and the mechanistic behaviors that may cause change.